A rare case of chronic ectopic pregnancy mimicking ovarian tumor: a diagnostic dilemma - Tigga, Maureen Prativa; Chakraborty, Salil Bindu; Ray, Jayanta; Debbarma, Sourish; Debbarma, Amulya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Clinical presentation of chronic ectopic pregnancy is often perplexing. The diagnosis becomes difficult due to paucity of classical signs and symptoms and at times the relevant investigations turn out to be falsely negative. We present one such case, reporting to our hospital which serves the underprivileged North Eastern population of India. The low resource set up led to limitations in our approach and here we point out the factors which led to the diagnostic dilemma. We are reporting this case because similar challenges can be faced by other clinicians who are working in set up like ours.